The Jesus files – probing the crime and trial of Jesus Christ - Musavengana, Clappaton (Midlands State University, 2018)
A hasty trial, judgement and sentence of Jesus attracted my attention into a close investigation of the nature of Jewish and Roman Judiciary systems. The death sentence which was passed on Jesus appears to have been based on fragile grounds, accusations which could not have worth a death sentence at all. This project seeks to find out or investigate the actual reason which led to Jesus’ death which might be beyond what is presented in the gospels. The paper gives a literary appreciation of the different accounts of Jesus’ trial provided by the gospel writers. Looking at first on the manner in which the trial was held, one finds that it was not procedural according to Hebrew and Roman judiciary systems. The study provides a critic to Jesus’ arrest, trial and sentence basing on the upheld Jewish and Roman trial systems. The paper will rely on data from both primary and secondary sources such as the bible, academic journals and other books on Jesus accounts.